Survival and causes of death among people with clinically diagnosed dementia with Lewy bodies: A multicenter cohort study. (12th October 2022) - Zuo, Meimei; Yue, Wenjie; Zhang, Ding; Liu, Shuai; Gan, Jinghuan; Wang, Xiao‐Dan; Wu, Hao; Ji, Yong
Abstract: Objective: A comprehensive study of the survival and causes of death of people with clinically diagnosed Dementia with Lewy bodies (DLB) were few. The aim of our study was to investigate the survival and causes of death of DLB. Methods: The patients diagnosed with probable DLB were consecutively enrolled from five memory clinics in China across a 5‐year period (2017–2021) with mortality data updated to December 2021. The endpoint was all‐cause death. Survival analysis including Cox regression by groups (time both from disease onset and the first visit to death) and causes of death were evaluated. Results: Of the 108 patients with DLB, 54 (50%) were men and the time from onset of disease to the first visit to the memory clinic (lag time) was 24 (12–48) months. During follow‐up, 28.7% ( n = 31) of the patients died. The median survival time both from disease onset and the first visit were 81 (95% cognitive impairment (CI) 69.09–92.91) and 45 (95% CI 34.78–55.22) months, respectively. The use of antipsychotic drugs (HR 0.15, 95% CI: 0.03–0.75), moderate to severe dementia (Clinical Dementia Rating [CDR]) at the first visit (HR 0.22, 95% CI 0.78 to 0.62) and the longer lag time (HR 0.943, 95% CI 0.92–0.97) predicted a shorter survival. Failure to thrive (stopped eating, drinking) or multiple organ dysfunction syndrome (MODS) maybe the most common cause of death (41.7%), followed by pneumonia or aspiration (29.2%). Conclusions: The factors associated with survival time were disease severity level, antipsychotic drug use and lag time to seek medical advice. Failure to thrive or MODS and pneumonia were probably the most common cause of death. The long‐term outcomes of DLB patients may be helpful to guide clinicians counseling patients and caregivers. Key points: Our study includes a multicenter and longitudinal study of the survival and probable causes of death of people with clinically diagnosed Dementia with Lewy bodies (DLB) in China. The factors associated with the survival times were more relevant to disease severity level, antipsychotic drug use and lag time to seek medical advice. The results can inform patient and family counseling and the patients' families of the opportunities for improved care at the end of life.